Silicon-carbon composite negative electrode material, and preparation method and application thereof

CN122889712APending Publication Date: 2026-10-09HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610739679.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-27
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

但目前将其应用于硅碳复合材料,特别是直接制备具有核壳结构的高性能硅碳复合材料的研究尚不充分,且如何通过精确调控工艺参数来解决硅碳均匀包覆、纳米硅分散以及首次库伦效率低等问题,仍是技术难点

Benefits of technology

1、结构独特,性能优异:通过喷雾裂解过程的自组装效应,自然形成了以纳米硅为核、无定形碳为壳的独特核壳结构。致密的碳壳能有效约束硅核的体积膨胀,防止纳米硅颗粒的团聚,并显著提高材料的导电性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889712A_ABST
    Figure CN122889712A_ABST
Patent Text Reader

Abstract

The application discloses a silicon-carbon composite negative electrode material and a preparation method and application thereof. The silicon-carbon composite negative electrode material provided by the application is a spherical secondary particle with a core-shell structure; the silicon-carbon composite negative electrode material comprises the following components: the core is a nanometer silicon spherical particle, and the shell is a carbon coating layer. The application ingeniously constructs a spherical core-shell structure with nanometer silicon as the core and amorphous carbon as the shell through one-step spray pyrolysis combined with secondary heat treatment. The structure can effectively relieve volume expansion, improve conductivity and initial efficiency. The application has the advantages of simple process, continuity and easy enlargement, the prepared material has the advantages of high specific capacity, high initial efficiency and long cycle life, and is suitable for high-performance lithium ion battery negative electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery anode material technology, specifically to a novel silicon-carbon composite anode material with low crystallinity for lithium-ion batteries, its preparation method, and its application. Background Technology

[0002] With the rapid development of electric vehicles and the large-scale energy storage market, the market has placed higher demands on the energy density of lithium-ion batteries. Silicon (Si) is considered the most promising next-generation high-energy-density lithium-ion battery anode material due to its extremely high theoretical specific capacity (approximately 4200 mAh / g, far exceeding graphite's 372 mAh / g), low delithiation potential, and abundant natural reserves.

[0003] However, silicon materials exhibit a severe volume effect during charge and discharge (expansion rate can reach over 300%), which leads to the pulverization and shedding of active materials and their continuous reaction with the electrolyte to form an unstable solid electrolyte interphase (SEI) film, resulting in rapid capacity decay and poor cycle life. Furthermore, silicon itself has poor conductivity, limiting its rate performance.

[0004] To overcome these drawbacks, researchers have proposed various strategies, among which constructing silicon-carbon composites is one of the most effective methods. The carbon matrix can effectively buffer the volume expansion of silicon, improve the conductivity of the composite material, and inhibit the excessive growth of the SEI film. Currently, the main methods for preparing silicon-carbon composites include mechanical ball milling, chemical vapor deposition (CVD), sol-gel methods, and high-temperature pyrolysis. However, these methods generally suffer from problems such as complex processes, high costs, difficulty in scaling up, or poor product uniformity.

[0005] Spray pyrolysis is a technique that atomizes a precursor solution into micron-sized droplets, which are then rapidly dried, pyrolyzed, and carbonized in a high-temperature reactor to ultimately form spherical powder materials. This method offers advantages such as continuous process, ease of scale-up, uniform product composition, and controllable morphology. However, its application to silicon-carbon composites, particularly the direct preparation of high-performance silicon-carbon composites with core-shell structures, remains insufficient. Furthermore, precisely controlling process parameters to address challenges such as uniform silicon-carbon coating, nano-silicon dispersion, and low initial coulombic efficiency remain key technical hurdles. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a novel silicon-carbon composite anode material, its preparation method, and its applications. The material exhibits good conductivity and coating processability, and its preparation method is simple, efficient, and easily scaled up for industrial applications.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a silicon-carbon composite anode material having a core-shell structure, wherein the core structure is nano-silicon spherical particles and the shell structure is a carbon coating layer; the silicon-carbon composite anode material consists of spherical secondary particles with a particle size distribution D. 50 The size ranges from 7.5 to 9.1 μm, and the molar ratio of carbon to silicon is 0.9 to 1.1.

[0008] In the silicon-carbon composite anode material of the present invention, the silicon spheres of its core structure are amorphous, thus exhibiting excellent electrochemical performance.

[0009] The silicon-carbon composite anode material of the present invention has a unique core-shell structure, with nano-silicon spherical particles as the core and a carbon coating layer as the shell. The dense shell layer effectively constrains the volume expansion of the silicon spheres and prevents them from agglomerating, thereby significantly improving the conductivity of the material. At the same time, the anode material is a spherical secondary particle with the advantages of narrow particle size distribution and good mobile phase, which is beneficial to the subsequent coating process of the electrode sheet.

[0010] Furthermore, the thickness of the carbon coating layer is 10-50 nm. In actual preparation, the thickness of the carbon coating layer can be controlled by adjusting the carbon content.

[0011] The carbon coating also includes a porous structure with an average pore diameter of 1.7 nm.

[0012] Secondly, the present invention provides a method for preparing the silicon-carbon composite anode material, comprising the following steps: S1. Atomize the precursor suspension containing silicon source and carbon source and carry out spray pyrolysis reaction; S2. The powder obtained from the reaction in step S1 is subjected to a second heat treatment to obtain the silicon-carbon composite anode material.

[0013] This invention significantly improves the density of the shell by combining spray pyrolysis reaction (plasticity) and secondary heat treatment (reduction), thereby effectively controlling the volume expansion of silicon cores, preventing the agglomeration of silicon particles, and thus significantly improving the conductivity of the material.

[0014] In step S1, the silicon source is nano-silicon powder with a particle size of 50-150nm, specifically 100nm; In step S1, the carbon source is one or more of sucrose, glucose, pitch, phenolic resin, polyacrylonitrile, and citric acid. In step S1, the mass ratio of the nano-silicon powder to the carbon source is 1:(0.5-3). In the actual preparation process, the mass ratio of silicon powder to carbon source can be adjusted according to the type of carbon source, so that the silicon-carbon ratio eventually reaches 1:1.

[0015] In step S1, the concentration of the precursor suspension is 10-30 g / L, preferably 15-25 g / L, and specifically 20 g / L. By controlling the concentration of the precursor suspension within this range, it is possible to ensure the formation of a spherical structure while also maintaining a certain degree of fluidity for easy processing.

[0016] In step S1, the atomization is achieved using an ultrasonic atomizer or a dual-fluid atomizer.

[0017] In step S1, the reaction conditions for the spray pyrolysis reaction are: a temperature of 600-1000℃, specifically 800-850℃, to avoid silicon powder agglomeration due to excessive temperature, and a time of 10-30s.

[0018] The conditions for the secondary heat treatment are as follows: temperature 800-1100℃, specifically 900-950℃, time 1-4 hours, time 2 hours, and heating rate 2-5℃ / min. The temperature of the secondary heat treatment is not lower than the temperature of the spray pyrolysis reaction to achieve complete carbonization while avoiding excessively high temperatures that could lead to silicon powder crystallization. Specifically, the temperature of the secondary heat treatment is 100-200℃ higher than that of the spray pyrolysis reaction.

[0019] As a specific embodiment of the present invention, the method is performed according to the following operations: 1) Add nano-silicon powder and carbon source to a solvent and disperse them to form a precursor suspension; the solvent is one or more of deionized water, ethanol or isopropanol; 2) The precursor suspension prepared in step 1) is transported to the atomizer of the spray pyrolysis reactor by a peristaltic pump for atomization; 3) Under an inert atmosphere, the aerosol droplets are carried by a carrier gas into a preheated tubular reactor for spray pyrolysis reaction; the gas flow rate is 5-20 L / min; the carrier gas is high-purity argon or nitrogen. 4) The gas-solid mixture coming out of the tubular reactor is collected by a filter to obtain primary powder. The collected primary powder is subjected to secondary heat treatment at 800-1100℃ for 1-4 hours under an inert atmosphere. After natural cooling, silicon-carbon composite anode material is obtained.

[0020] The precursor suspension also includes a pore-forming agent; the pore-forming agent is magnesium powder or zinc powder, and its addition amount is 1-5% of the carbon source mass. After the secondary heat treatment, an acid washing step is added to remove the oxides formed by the pore-forming agent, thereby introducing mesopores into the carbon shell and improving ion transport kinetics.

[0021] Thirdly, the present invention provides a lithium-ion battery, including a negative electrode; the material of the negative electrode is the silicon-carbon composite negative electrode material or the silicon-carbon composite negative electrode material obtained by the preparation method.

[0022] Specifically, the lithium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode is made of an active material, a conductive agent, and a binder; The active material is the silicon-carbon composite material used in lithium-ion batteries.

[0023] In this invention, the positive electrode, separator, and electrolyte of the lithium-ion battery are all conventional electrodes or materials in the art. Specifically, the positive electrode can be a lithium sheet, the electrolyte is a 1 mol / L LiPF6 EC (ethylene carbonate) + DMC (dimethyl carbonate) solution, EC:DMC=1:1, and the separator is a PP (polypropylene) separator.

[0024] In this invention, the conductive agent and binder used in the negative electrode of the lithium-ion battery are conventional materials in the art, specifically super-P (superconducting carbon black) conductive agent and PVDF (polyvinylidene fluoride) binder.

[0025] Compared with the prior art, the beneficial effects achieved by the present invention are: 1. Unique structure and superior performance: Through the self-assembly effect of the spray pyrolysis process, a unique core-shell structure is naturally formed, with nano-silicon as the core and amorphous carbon as the shell. The dense carbon shell can effectively constrain the volume expansion of the silicon core, prevent the agglomeration of nano-silicon particles, and significantly improve the conductivity of the material.

[0026] 2. Uniform morphology and good dispersibility: The obtained product is spherical secondary particles with narrow particle size distribution and good flowability, which facilitates the subsequent coating process of electrode sheets.

[0027] 3. One-step synthesis, simple process: The drying, pyrolysis and carbonization processes are integrated into one reactor through spray pyrolysis technology, which simplifies the process flow, improves production efficiency, and makes it easy to achieve continuous large-scale production.

[0028] 4. High controllability: By adjusting parameters such as precursor concentration, carbon-silicon ratio, and reaction temperature, the particle size, carbon shell thickness, and final electrochemical performance of the product can be easily controlled. Attached Figure Description

[0029] Figure 1 The image shows the Raman spectrum of the novel low-crystallinity silicon-carbon composite material prepared in Example 1 of this invention.

[0030] Figure 2 This is a 20,000x scanning electron microscope image of the novel low-crystallinity silicon-carbon composite material prepared in Example 1 of this invention.

[0031] Figure 3 This is a 10,000x scanning electron microscope image of the novel low-crystallinity silicon-carbon composite material prepared in Example 1 of the present invention.

[0032] Figure 4 The charge-discharge curves of the novel low-crystallinity silicon-carbon composite material prepared in Example 1 of this invention at a current density of 0.05C.

[0033] Figure 5 The cycling performance curve of the novel low-crystallinity silicon-carbon composite material prepared in Example 1 of this invention at a 1C rate is shown. Detailed Implementation

[0034] The present invention will be further described below with reference to specific embodiments, but the present invention is not limited to the following embodiments.

[0035] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0036] Unless otherwise specified, all reagents, materials, instruments, etc. used in the following examples are commercially available.

[0037] Example 1 This embodiment provides a method for preparing a silicon-carbon composite anode material, and the specific operation steps are as follows: (1) Weigh 2g of nano-silicon powder with an average particle size of 100nm and 2g of sucrose (carbon source), and dissolve them in 200mL of a mixed solvent of deionized water and ethanol (volume ratio 1:1); mechanically stir the above mixture for 4 hours and then ultrasonically disperse it for 2 hours to form a uniform and stable precursor suspension with a concentration of 20 g / L.

[0038] (2) The precursor suspension was loaded into the reactor of the spray pyrolysis unit and atomized using an ultrasonic atomizer. High-purity nitrogen gas with a flow rate of 10 L / min was used as the carrier gas to carry the atomized droplets into a tubular furnace reactor heated to 850°C for 30 s. The product after the reaction was collected by a downstream filter cartridge collector to obtain a black powder.

[0039] (3) The collected black powder was heated to 950℃ at a rate of 3℃ / min under nitrogen protection and held at that temperature for 2 hours for a second heat treatment, followed by natural cooling. The cooled sample was then ground and sieved to obtain the final silicon-carbon composite anode material. Its specific surface area was measured to be 1.81 m². 2 / g, with a silicon-to-carbon molar ratio of 1:1.

[0040] The silicon-carbon composite material obtained in Example 1 was tested, and the results are as follows.

[0041] 1. Structural features like Figure 1 As shown, in the Raman image of the silicon-carbon composite material obtained in Example 1, all the characteristic peaks of silicon are peaks of amorphous silicon, which indicates that the silicon in the material exists in an amorphous state with excellent electrochemical performance.

[0042] like Figure 2 and Figure 3 As shown, the SEM image of the silicon-carbon composite material obtained in Example 1 shows micron-sized spherical particles, confirming that the preparation method provided by the present invention can directly convert the mixed suspension into a silicon-carbon anode material with high sphericity, and that the method is feasible.

[0043] 2. Electrochemical performance The electrochemical performance of the obtained negative electrode material was tested using a coin cell as a half-cell system, which is conventional in this field.

[0044] like Figure 4 As shown, the reversible capacity of the silicon-carbon composite material obtained in Example 1 is 1442.1 mAh / g, and the first-efficiency is 83.5%, which indicates that the spherical silicon-carbon anode can maintain a high first-efficiency of more than 80% while having a high reversible capacity.

[0045] like Figure 5 As shown, after 200 cycles at 1C, the capacity retention rate of the silicon-carbon composite material obtained in Example 1 is still as high as 70% or more.

[0046] Example 2 The difference from Example 1 is that 0.1 g of magnesium powder (5% of the sucrose mass) was added to the precursor solution as a pore-forming agent. Subsequent steps were the same as in Example 1. After a second heat treatment, the product was washed with 1M dilute hydrochloric acid to remove the magnesium oxide template, then washed with deionized water until neutral and dried.

[0047] Testing revealed that the obtained material, while maintaining its core-shell structure, exhibited a porous structure on the carbon shell, with an average porosity of 1.7 nm.

[0048] Example 3 The difference from Example 1 is that the concentration of the precursor suspension is 10 g / L; Example 4 The difference from Example 1 is that the concentration of the precursor suspension is 30 g / L; Example 5 The difference from Example 1 is that the spray pyrolysis reaction temperature is 1000°C, and the secondary heat treatment condition is 1100°C.

[0049] Example 6 The difference from Example 1 is that the pore-forming agent is zinc powder, and its addition amount is 1%.

[0050] Comparative Example 1 The difference from Example 1 is that the precursor suspension was directly pyrolyzed at high temperature, specifically at 1000°C for 2 hours. The resulting material had an uneven morphology, with silicon particles agglomerated and carbon materials separated.

[0051] Comparative Example 2 The traditional mechanical ball milling method was used: equal amounts of nano-silicon powder and sucrose were mixed by high-energy ball milling for 4 hours, and then calcined at 900℃ for 4 hours under a nitrogen atmosphere. The resulting product had an uneven morphology, with uneven mixing of silicon and carbon, and some exposed silicon.

[0052] Performance testing: The materials obtained in Examples 2-6 and Comparative Examples 1-2 were tested using the same structural features and electrochemical performance testing methods as in Example 1 above, and the results are as follows.

[0053] Table 1. Detection results of silicon-carbon anode materials

[0054] Table 1 Analysis Results: Comparing Examples 1-6 with Comparative Examples 1-2, it can be seen that the silicon-carbon anode materials obtained in Examples 1-6 are all spherical secondary particles with a particle size D. 50 It exhibits a narrower distribution, lower resistivity, and higher initial and reversible capacities. Specifically, compared to Example 1, Examples 2 and 6 added a pore-forming agent, further enhancing the reversible capacity.

[0055] In summary, this invention utilizes the self-assembly effect of the spray pyrolysis process to naturally form a unique core-shell structure with nano-silicon as the core and amorphous carbon as the shell. A secondary heat treatment further forms a dense carbon shell, effectively constraining the volume expansion of the silicon core, preventing the agglomeration of nano-silicon particles, and significantly improving the material's conductivity. The resulting product consists of spherical secondary particles with a narrow particle size distribution and good flowability, facilitating subsequent electrode coating. Furthermore, this invention integrates drying, pyrolysis, and carbonization processes into a single reactor in one step using spray pyrolysis technology, simplifying the process flow, improving production efficiency, and facilitating continuous large-scale production.

[0056] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.

Claims

1. A silicon-carbon composite anode material having a core-shell structure, characterized in that, include: The core structure consists of nano-silicon spherical particles, and the shell structure consists of a carbon coating layer. The silicon-carbon composite anode material consists of spherical secondary particles with a particle size distribution D. 50 The range is 7.5-9.1 μm.

2. The silicon-carbon composite anode material according to claim 1, characterized in that, The thickness of the carbon coating layer is 10-50 nm.

3. The silicon-carbon composite anode material according to claim 1 or 2, characterized in that, The carbon coating also includes a porous structure.

4. The method for preparing the silicon-carbon composite anode material according to any one of claims 1-3, characterized in that, Includes the following steps: S1. Atomize the precursor suspension containing silicon source and carbon source and carry out spray pyrolysis reaction; S2. The powder obtained from the reaction in step S1 is subjected to a second heat treatment to obtain the silicon-carbon composite anode material.

5. The preparation method according to claim 4, characterized in that, In step S1, the silicon source is nano-silicon powder with a particle size of 50-150 nm; The carbon source is one or more of sucrose, glucose, pitch, phenolic resin, polyacrylonitrile, and citric acid. The mass ratio of the nano-silicon powder to the carbon source is 1:(0.5-3).

6. The preparation method according to claim 4, characterized in that, In step S1, the concentration of the precursor suspension is 10-30 g / L; The atomization is achieved using an ultrasonic atomizer or a dual-fluid atomizer.

7. The preparation method according to claim 4, characterized in that, In step S1, the reaction conditions for the spray pyrolysis reaction are: temperature of 600-1000℃ and time of 10-30s.

8. The preparation method according to claim 4, characterized in that, In step S2, the conditions for the secondary heat treatment are: temperature of 800-1100℃, time of 1-4h, and heating rate of 2-5℃ / min. The temperature of the secondary heat treatment is not lower than the temperature of the spray pyrolysis reaction.

9. The preparation method according to claim 4, characterized in that, The method is performed as follows: 1) Add nano-silicon powder and carbon source to a solvent and disperse them to form a precursor suspension; 2) The precursor suspension is transported to the atomizer of the spray pyrolysis reactor for atomization to form aerosol droplets; 3) Under the protection of an inert atmosphere, the aerosol droplets are carried by a carrier gas into a preheated tubular reactor for spray pyrolysis reaction to obtain primary powder; 4) Under the protection of an inert atmosphere, the primary powder undergoes a secondary heat treatment and is cooled to obtain a silicon-carbon composite anode material.

10. The preparation method according to any one of claims 4-9, characterized in that, The precursor suspension also includes a pore-forming agent; The pore-forming agent is magnesium powder or zinc powder, and its addition amount is 1-5% of the mass of the carbon source.

11. The preparation method according to claim 10, characterized in that, After the secondary heat treatment, an acid washing step is added.

12. A lithium-ion battery, characterized in that, Includes a negative electrode; the material of the negative electrode is the silicon-carbon composite negative electrode material according to any one of claims 1-3 or the silicon-carbon composite negative electrode material obtained by the preparation method according to any one of claims 4-11.